Programmed death‐ligand 1 expression in Epstein‐Barr virus positive nasopharyngeal cancer - Abdulhameed Alfagih; Muhammad Amin Ur Rahman; Sadeq Al‐Dandan; Salem Alrehaili; Tariq Wani; Abdulrahim Al Malki; Ali Al Zahrani; Hatoon Bakhribah (ImmunoMedicine, 2023)
Abstract Nasopharyngeal cancer (NPC) is common in Saudi Arabia; Most cases are related to the Epstein‐Barr virus (EBV), which is associated with treatment failure and a high recurrence rate. Programmed cell death protein 1 (PD‐1) and Programmed death‐ligand 1 (PD‐L1) inhibitors emerged as breakthroughs in cancer treatment, including head and neck cancers. The benefit of these therapies was seen in patients with high expression of PD‐L1, which is unknown in our population.  We aim to assess PD‐L1 expression in EBV‐related NPC patients presented to King Fahd Medical City (KFMC). We identified 41 cases of EBV‐related NPC diagnosed between 2016 and 2019. PD‐L1 expression was assessed using the Tumor Proportion Score (TPS) and Combined Positive Scores (CPS). Results showed that PD‐L1 expression was negative in 51% and 29% using TPS and CPS scores, respectively. High expression of PD‐L1, more than 50%, was seen in 17% using TPS and 22% using CPS. There was no statistically significant correlation between the degree of PD‐L1 expression by TPS or CPS and many variables, including gender, comorbidities, BMI, TNM staging, and smoking status. Over a median follow‐up of 29.7 months, Kaplan‐Meier survival curves did not show a statistically significant difference between all groups of PD‐L1 expression for O.S. or PFS; However, there were shorter O.S noted with CPS 1%–9%, log‐rank p‐value = 0.031. These findings support investigating the role of Immunotherapy, especially in the high expression subgroup. Data for these patients' outcomes and further studies to explore the role of PD‐L1 in NPC are needed.